1994
DOI: 10.1111/j.2044-8341.1994.tb01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Belief in demons and exorcism in psychiatric patients in Switzerland

Abstract: Belief in demons as the cause of mental health problems is a well-known phenomenon in many cultures of the world. However, there is little literature on this phenomenon in Protestant subcultures of the West. The author conducted a systematic investigation of the prevalence of this attribution in 343 mainly Protestant out-patients of a psychiatric clinic in Switzerland, who described themselves as religious. Of these, 129 (37.6 per cent) believed in the possible causation of their problems through the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 14 publications
1
28
1
5
Order By: Relevance
“…Some Western cultures hold this idea too. A study conducted in Switzerland, with psychiatric patients, revealed that demons were considered the main cause of mental health problems 14. A South Asian study revealed that people there perceive mental illness as natural part of the suffering that is predestined for them.…”
Section: Introductionmentioning
confidence: 99%
“…Some Western cultures hold this idea too. A study conducted in Switzerland, with psychiatric patients, revealed that demons were considered the main cause of mental health problems 14. A South Asian study revealed that people there perceive mental illness as natural part of the suffering that is predestined for them.…”
Section: Introductionmentioning
confidence: 99%
“…Beliefs in supernatural causes for mental illness are widespread in Africa [3,5] and are even present in western societies [10]. Though those that hold such beliefs are sometimes in the minority [4], some of these beliefs promote stigma and discrimination [5].…”
Section: Discussionmentioning
confidence: 99%
“…(c) They declared their desire to consult a psychiatrist who showed an understanding attitude towards their faith. Further details of the sample have been described elsewhere [23]. The topic of the demonic was explored in the course of semistructured interviews on admission or in the course of therapy.…”
Section: Methodsmentioning
confidence: 99%